2012
DOI: 10.1007/s00213-012-2904-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mood stabilizers on marble-burying behavior in mice

Abstract: These results suggest that GABAergic mechanism is involved in marble-burying behavior, and that valproate, carbamazepine and lamotrigine reduce marble-burying behavior. Moreover, valproate reduces marble-burying behavior via a GABA(A) receptor-dependent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Meanwhile, Usp46 -deficient mice exhibited significantly higher scores than WT mice in the marble burying test. Marble burying behavior is thought to be a pharmacological model for obsessive-compulsive disorder [29], and this behavior is also regulated by the GABAergic system [30]. Taken together, these results suggest that Usp46 controls a broad range of behavioral phenotypes, and presently, it is difficult to extrapolate the behavioral phenotype of Usp46- deficient mice to any specific mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Usp46 -deficient mice exhibited significantly higher scores than WT mice in the marble burying test. Marble burying behavior is thought to be a pharmacological model for obsessive-compulsive disorder [29], and this behavior is also regulated by the GABAergic system [30]. Taken together, these results suggest that Usp46 controls a broad range of behavioral phenotypes, and presently, it is difficult to extrapolate the behavioral phenotype of Usp46- deficient mice to any specific mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that marble-burying persists over repeated exposure, even when avoidance of the marbles is possible and after animals have been habituated to the presence of marbles in their home cage environments for extended periods (Njung'e & Handley, 1991b;Thomas et al, 2009). Moreover, the facts that marble-burying correlates poorly with the outcomes of other classical experimental tests of anxiety (Sanathara et al, 2018;Savy et al, 2015;Thomas et al, 2009; although see also Greene-Schloesser et al, 2011) and that it is subject to significant between-strain variation (Angoa-PĂŠrez, Kane, Briggs, Francescutti, & Kuhn, 2013;Egashira et al, 2013;Nicolas et al, 2006;Thomas et al, 2009) further suggest that marble-burying as it is normally carried out in the lab-that is, not based on individual differences in behavior, but rather to characterize group differences in supposed abnormal burying behavior, mostly following drug intervention-represents an inherent, rather than a neophobic or anxiety-related, behavioral phenotype. As such, the MBT has since been employed to model the purported behavioral manifestations of OCD-that is, seemingly purposeless repetition Gaikwad, Parle, Kumar, & Gaikwad, 2010;Iijima, Kurosu, & Chaki, 2010;Taylor et al, 2017;Umathe, Bhutada, Dixit, & Shende, 2008;Umathe et al, 2012); in most cases, however, this approach is also unjustified, as will be explained.…”
Section: The Mbt: a Brief History And Proof Of Conceptmentioning
confidence: 99%
“…Investigations into MBA that have also reported results from locomotor assessments have employed several approaches, including separate analyses of LMA (Krass et al, 2010;Millan et al, 2002;Saadat et al, 2006) and simultaneous recording of marble-burying and LMA (Egashira et al, 2018;Jimenez-Gomez et al, 2011;Matsushita et al, 2005;Nicolas et al, 2006). Furthermore, LMA assessments may employ either the same subjects tested for marble-burying behavior (Egashira et al, 2013;Schneider & Popik, 2007;Umathe, Vaghasiya, Jain, & Dixit, 2009) or a separate group exposed to treatment regimens analogous to that of the group tested for burying behavior (Gaikwad et al, 2010;Saadat et al, 2006;Uday et al, 2007). Considering that marble-burying behavior may involve preoccupation with objects, it is possible that simultaneous measurements of burying and locomotion may yield inappropriate results, since animals engaging in burying activity may travel shorter overall distances than animals engaging in normal exploratory routines (de Brouwer & Wolmarans, 2018).…”
Section: Locomotor Performancementioning
confidence: 99%
“…It is well established that a plausible cause of OCD is abnormal cortical-striatal-thalamic circuitry activation (Ahmari et al, 2013) and altered serotonergic (Schilman et al, 2010), glutamatergic (Arnold et al, 2004; Egashira et al, 2013; Porton et al, 2013) and GABAergic (Egashira et al, 2013) systems. Interestingly, female hormones, such as estrogen and P4, regulate various neurotransmitter signaling pathways in brain regions implicated in OCD (Dreher et al, 2007; Karakaya et al, 2007; Benmansour et al, 2009; Alonso et al, 2011; Quinlan et al, 2013; Barth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%